Βook Review: S. NEOCLEOUS, Heretics, Schismatics, or Catholics? Latin Attitudes to the Greeks in the Long Twelfth Century, Toronto: Pontifical Institute of Mediaeval Studies, 2019 - ΤΟΥΝΤΑ, Ελένη (Byzantina Symmeikta, 2020)
Book Review: S. Neocleous, Heretics, Schismatics, or Catholics? Latin Attitudes to the Greeks in the Long Twelfth Century, Toronto: Pontifical Institute of Mediaeval Studies, 2019